Measurement of the top quark mass with the template method in the t(t)over-bar -> lepton plus jets channel using ATLAS data - Onofre, A. (2012)
This paper describes an analysis of the angular distribution of W→eν and W→μν decays, using data from pp collisions at s√=7 TeV recorded with the ATLAS detector at the LHC in 2010, corresponding to an integrated luminosity of about 35 pb−1. Using the decay lepton transverse momentum and the missing transverse momentum, the W decay angular distribution projected onto the transverse plane is obtained and analysed in terms of helicity fractions f0, fL and fR over two ranges of W transverse momentum (pWT):35<pWT<50 GeV and pWT>50 GeV. Good agreement is found with theoretical predictions. For pWT>50 GeV, the values of f0 and fL−fR, averaged over charge and lepton flavour, are measured to be: f0=0.127±0.030±0.108 and fL−fR=0.252±0.017±0.030, where the first uncertainties are statistical, and the second include all systematic effects.